The Effect of Ultraviolet Radiation on Photosynthetic pigments in Euglena gracilis - Ayash, Abdulkarim; Mohammad , Issam; Nassour, Rana (Latakia University Journal -Basic Sciences Series, 2018)
The study was conducted during 2017 in the laboratories of the department of Botany at Tishreen University, Lattakia, Syria. The effect of ultraviolet radiation (UV-C and UV-B) for different periods (0.5, 1, 3, 5, 15, 15, 30, 45, 60 minutes) on the photosynthetic pigments of Euglena gracilis (with three stages of measurements) was studied. The results showed that chlorophyll pigments were more sensitive to UV-C compared to UV-B. These reductions were correlated with the increase in the exposure time, reaching the lowest value after 60 minutes exposure (97.83, 98.73, 99.18% for chlorophyll a, chlorophyll b and carotenoids when measured after 24 hours respectively). The polyethylene films protect the chlorophyll pigments against UV radiation. The protection rate was more evident against UV-C reaching 7.78% after 24 hours in the algae exposed for 30 minutes according to the experimental conditions.